1994
DOI: 10.1177/095646249400500305
|View full text |Cite
|
Sign up to set email alerts
|

Double-Blind, Randomized Clinical Trial on the Effect of Interferon-Beta in the Treatment of Condylomata Acuminata

Abstract: A randomized, double-blind, placebo-controlled trial was conducted to assess interferon-beta efficacy and safety in the treatment of anogenital condylomatous lesions. One hundred patients received a daily intramuscular injection of either interferon-beta (IFN-beta) (2 MIU/day) or placebo for 10 days. Of 94 evaluable patients, the complete response rate observed 8 weeks after treatment was significantly higher in the group receiving IFN-beta, as compared to the placebo-treated group (51% vs 28.9%, P < 0.05). Af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…Finally, we included 12 studies, which involved a total of 1445 patients. Among them, 11 were published in English [18-28], 1 in Chinese(available only by searching the database of CNKI). Apart from Chinese and English, we did not search citations in other languages.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, we included 12 studies, which involved a total of 1445 patients. Among them, 11 were published in English [18-28], 1 in Chinese(available only by searching the database of CNKI). Apart from Chinese and English, we did not search citations in other languages.…”
Section: Resultsmentioning
confidence: 99%
“…This could be confirmed by the 20-30% rate of spontaneous remission during the first year of infection among otherwise healthy patients, and, on the other hand by the extensive refractory disease observed among immunosuppressed patients [28,29]. Conventional treatments for genital warts, including physical or chemical ablation of warts, may cause local issues such as inflammation, pain, ulceration or scars [30].…”
Section: Discussionmentioning
confidence: 99%
“…At day 22, (table) a total of 72 lesions had been treated and observed. Of these, 15/24 (63%) of lesions injected with 1 x 106 IU r-hIFN-beta showed a CR, compared with 9/24 (38%) and 5/24 (21%) injected with 33,000 IU r-hIFN-beta and placebo respectively. The number of CRs resulting from the higher dose was significantly higher than that resulting from treatment with placebo (p = 0.0063, McNemar test, two-sided), while not significantly different from the lower dose (p = 0 34, McNemar test).…”
Section: Resultsmentioning
confidence: 96%
“…We thank Dr I Trinchard-Lugan for monitoring the study, and Dr PE Engrand for assisting in the interpretation of data.This trial was sponsored by a grant from Ares-Serono SA, 15 bis, chemin des Mines, 1202 Geneva, Switzerland.…”
mentioning
confidence: 99%
“…Placebo controlled randomized trials have generally found intralesional therapy to be most effective, 52 while evidence for the efficacy of systemic and topical therapy has been inconsistent. [53][54][55][56] Intralesional injection of 0.5 to 1.5 million international units per lesion is administered two to three times per week for up to three weeks. The course of therapy can be repeated 12 to 16 weeks from the initial treatment.…”
Section: Interferonsmentioning
confidence: 99%